Long‐term live‐cell imaging reveals new roles for Salmonella effector proteins SseG and SteA. (28th July 2016) - McQuate, Sarah E.; Young, Alexandra M.; Silva‐Herzog, Eugenia; Bunker, Eric; Hernandez, Mateo; de Chaumont, Fabrice; Liu, Xuedong; Detweiler, Corrella S.; Palmer, Amy E.
Summary: Salmonella Typhimurium is an intracellular bacterial pathogen that infects both epithelial cells and macrophages. Salmonella effector proteins, which are translocated into the host cell and manipulate host cell components, control the ability to replicate and/or survive in host cells. Due to the complexity and heterogeneity of Salmonella infections, there is growing recognition of the need for single‐cell and live‐cell imaging approaches to identify and characterize the diversity of cellular phenotypes and how they evolve over time. Here, we establish a pipeline for long‐term (17 h) live‐cell imaging of infected cells and subsequent image analysis methods. We apply this pipeline to track bacterial replication within the Salmonella ‐containing vacuole in epithelial cells, quantify vacuolar replication versus survival in macrophages and investigate the role of individual effector proteins in mediating these parameters. This approach revealed that dispersed bacteria can coalesce at later stages of infection, that the effector protein SseG influences the propensity for cytosolic hyper‐replication in epithelial cells, and that while SteA only has a subtle effect on vacuolar replication in epithelial cells, it has a profound impact on infection parameters in immunocompetent macrophages, suggesting differential roles for effector proteins in different infection models.